Answer:
see below
Explanation:
Simplify the following:
(6 - 2) (x^2)^2 + 7
6 - 2 = 4:
4 (x^2)^2 + 7
Multiply exponents. (x^2)^2 = x^(2×2):
4 x^(2×2) + 7
2×2 = 4:
Answer: 4 x^4 + 7
______________________________________________
Simplify the following:
13 (2 + 4)
2 + 4 = 6:
13×6
13×6 = 78:
Answer: 78
______________________________________________
12 + 0 =12 = True
______________________________________________
Simplify the following:
63/7 + 3×5
The gcd of 63 and 7 is 7, so 63/7 = (7×9)/(7×1) = 7/7×9 = 9:
9 + 3×5
3×5 = 15:
9 + 15
| 1 |
| 1 | 5
+ | | 9
| 2 | 4:
Answer: 24
_____________________________________________________
15 x 0 = 0 True
______________________________________________________
6 x 5 = 5 x 6 True
______________________________________________________
(6 x 3) x 5 = 6 x (3 x 5) True
______________________________________________________
4 + (6 + 2) = (4 + 6) + 2 True